"Every death matters?": Combat casualties, role conception, and civilian control. (23rd February 2022) - Mukherjee, Anit
Abstract: How do combat missions, defined as an armed confrontation that causes casualties, shape civil-military relations and military's role conception? This article argues that militaries that incur combat casualties gain a stronger hand in the civil-military equilibrium. This is because casualties affect domestic political opinion and give prominence to the views expressed by military officials. Civilians are then more deferential to professional military advice. In turn, the military obtains considerable operational freedom, and can pick and choose missions which they find desirable. Second, the military's role conception – an important determinant of military missions, is shaped most prominently by its combat experience. Militaries sustaining casualties obtain leverage vis-à-vis civilians and based on their institutional preference, they either prioritise or avoid non-traditional missions. While making these arguments, this article examines combat casualties, role conception, and civilian control in India. These concepts as a whole and, the Indian case study especially are surprisingly understudied considering it is among the few non-Western democracies with firm civilian control, a record of overseas intervention operations and a military with varying roles and missions. Analysing India's experience therefore adds to the literature and illuminates the mechanism through which casualties affect civil-military relations.